Strategic reorganisation – impact on antenatal screening service for first trimester combined test in down's syndrome. (7th June 2011) - Ghosh, M; Baker, J; Finn, J; Phillips, A; Churchill, D
Abstract : Introduction: The UK National Screening Committee (NSC) recommended the first trimester combined test as a screening tool for Down' syndrome in 2007. While the test was available in private healthcare, implementation within the NHS faced challenges. Our unit at New Cross Hospital, Wolverhampton, took the initiative in West Midlands to introduce the combined test in October 2008. Method: The reorganisation was planned by a team from fetal medicine, ultrasonography and midwifery. The change was implemented after a year. New screening pathway was developed to address changes in antenatal referral and appointment system. New information leaflets and consent forms were introduced. All staff received training on Down's screening. All women were offered first trimester screening if the gestation was between 11 and 13+6 weeks and the CRL measurement was between 42 and 79 mm. Results: Table 1 shows uptake of first and second trimester screening during the first year of introduction. The uptake rate for diagnostic procedure following the screening was 56%. The detection rate was 80% and false positive rate was 2.6%. This met the benchmark laid by NSC in 'Model of Best Practice'. Comment: The above exercise proves that the service can be provided within the financial and delivery constraints of NHS. An inequality affecting the local population in having access to best screening programme was resolved.